Education [Bildung]–Literality–Competence: On Competing Tasks of Public Schools and the Need for New Links Between Teaching and Educational Research - Benner, Dietrich (ECNU Review of Education, 2023)
Purpose: The article distinguishes between the three concepts of standardization of the tasks of pedagogical action in modern educational systems: - the traditional concept of standardizing educational goals through curricula, - the literacy concept of psychometric standardization, - and the concept of competence, which can be developed in different ways. Design/Approach/Methods: I examine these concepts and show - that traditional curricular orientations suffer from the fact that they have not developed controls over the achievement of objectives, - that literacy concept allows for psychometric measurement, but this is not coordinated with the actual teaching and its goals, - and that competence models only offer further possibilities if their subject-specific requirements are aligned with the educational theoretical and didactic teaching objectives. Findings: Instead of replacing traditional input control with output measurements, it is important to link teaching and educational research in such a way that competence measurements not only measure the levels of demands achieved by learners but also the quality and effectiveness of teaching. Originality/Value: The train of thought overcomes the juxtaposition of philosophy of education and empirical research and shows how the two can cooperate theoretically and empirically.